ACTIVATING THE MORAL SELF-DEVELOPMENT IN THE PROCESS OF ETHICS EDUCATION AND CULTURE STUDIES - A. S. Frants; O. P. Belkina (Образование и наука)
The paper considers the problem of young people’s moral education with the reference to the system of secondary vocational education; the relevance of the study being enhanced by the greater independence of vocational college students compared to their high school peers. In addition, the paper describes the psychological and pedagogical difficulties in developing the moral norms, behavior principles, and life position in adolescence, when a mere moral declaration has little effect. Taking into consideration the students’ psychological and age characteristics, the authors suggest the active methods of dialogical interactions and recommend the system of ethical education and culture studies based on a differentiated understanding of specificity of the domestic moral culture, and axiological analysis of its educational potential. The multi-variant moral norms coexisting in modernRussiainclude the traditional, aristocratic, pragmatic and other types of values; all of them can be introduced in the series of educational discussions. The paper lists the approximate topics for such ethical and cultural debates, and demonstrates the expected effect of students’ moral self-assessment related to their life position and behavior patterns. The recognized moral values are likely to make a foundation for the students’ proper behavior both in college and in their future work.